THE ANALYSIS OF PHARMACEUTICAL ASPECT OF PRESCRIPTIONS FOR PEDIATRIC PATIENTS IN SUNGAI TUTUNG HEALTH CARE: PRESCRIPTIONS - Iisma Rizki Fadhila; Rahmadevi Rahmadevi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Pharmaceutical care for pediatric patients requires high accuracy because drug dosage must be adjusted according to age, body weight, and physiological conditions. This study aimed to evaluate the validity of compounded prescriptions for pediatric patients at Sungai Tutung Public Health Center in 2024 based on pharmaceutical aspects, particularly dosage appropriateness. Methods: This study used a descriptive observational design with a retrospective approach. The sample consisted of 60 pediatric compounded prescriptions with 162 drug items. Data were analyzed using descriptive quantitative analysis. Results: The results showed that 42 prescriptions, or 70.0%, were categorized as valid, while 18 prescriptions, or 30.0%, were invalid. Children aged 2–5 years were the most frequent group receiving compounded prescriptions, accounting for 56.7%. Of 162 drug items, 140 items, or 86.4%, had appropriate dosages, while 22 items, or 13.6%, were overdosed. Dosage discrepancies were found in ranitidine, chlorpheniramine maleate, and guaifenesin. Conclusion: This study concludes that the sensuality of pediatric compounded prescriptions was generally adequate; however, improved prescription accuracy and strengthened screening by pharmaceutical personnel are still needed.